Honey Plants of Düzce University Ornamental and Medicinal Plants Botanical Garden - Salih Sercan Kanoğlu; Ahmet Ayteğin; Tuba Gül Doğan; Nermin Başaran; Serdar Aslan; Sertaç Kaya; Murat Sargıncı; Bilal Çetin; Şemsettin Kulaç; Ozgur Yerlı; Bilge Tunçkol; Nihan Koçer; et al. (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
In this study, melliferous plants that the honey bee (Apis mellifera L.) can benefit from among the taxa planted in Düzce University Ornamental and Medicinal Plants Botanical Garden, are presented. Among the 451 taxa planted in the botanical garden, those with these characteristics were determined by reviewing studies on the subject. Of the 165 taxa (36.58%) included in the honey plant class; 119 contain both nectar and pollen, 25 contain pollen, 13 contain nectar, 4 contain both pollen and insect secretion (IS) or sweet sap (SS), 2 contain pollen, nectar and IS or SS, 1 contain both nectar and SS, 1 contain only IS. In order to prevent the decrease in pollinator and pollinator insects, whose numbers are decreasing due to global climate change, a "Bee and Insect Hotel" was placed in the botanical garden. For this reason, the majority of the plants selected for planting were chosen from taxa with honey plant properties. The main purpose here is both to pollinate the plants in the botanical garden and to show and explain the effects of insect species on pollination through nature education.